2006
DOI: 10.1097/01.hjh.0000222752.67572.61
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension prevalence, awareness, control and association with metabolic abnormalities in the San Marino population: the SMOOTH study

Abstract: Even in a small Mediterranean country with high health-care standards, hypertension awareness, treatment and control are inadequate and hypertension clusters with metabolic abnormalities and risk factors as in non-Mediterranean areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
41
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 39 publications
12
41
1
2
Order By: Relevance
“…15 Other European and American studies have similarly reported that around 25% of all hypertensives and 50% of treated patients have controlled blood pressure, [15][16][17] although further European studies have suggested that these figures may overestimate rates of control. [18][19][20][21] In South Africa, only 14% of hypertensives had adequately controlled blood pressure. 22 This gap between our ability to prevent and treat hypertension and the actual levels of control achieved constitutes a significant failing of public health management and health care worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…15 Other European and American studies have similarly reported that around 25% of all hypertensives and 50% of treated patients have controlled blood pressure, [15][16][17] although further European studies have suggested that these figures may overestimate rates of control. [18][19][20][21] In South Africa, only 14% of hypertensives had adequately controlled blood pressure. 22 This gap between our ability to prevent and treat hypertension and the actual levels of control achieved constitutes a significant failing of public health management and health care worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in both Europe and the United States have reported that only around 25% of all hypertensives and 50% of treated patients have controlled blood pressure, [4][5][6][7] while further European studies have suggested that true rates of control may be significantly lower. [8][9][10] The reasons for poor blood pressure control rates are complex. In part, they reflect the impact of structural and economic factors on access to health care, but local clinical, prescriber and patient factors that undermine the adequacy of treatment are also significant.…”
Section: Introductionmentioning
confidence: 99%
“…9-11 Previous research focused on only a few additional risk factors screened in primary care clinics, 7 generally lipids and glucose profile, or reported the association of BP control with lifestyle and some metabolic abnormalities in clinical settings. 8,[12][13][14][15] Lastly, little is known as to whether the diagnosis of hypertension is related to the degree of attainment of cardiometabolic goals.In this study, we examined the nationwide degree of awareness of hypertension in the adult population of Spain and the achievement of cardiometabolic goals according to awareness of the hypertensive condition of the individuals. We also presented the prevalence and control of all hypertensive patients.…”
mentioning
confidence: 99%